Malignant fibrous histiocytoma of the scalp: A rare differential with a dramatic clinical presentation - Krishnamurthy, Arvind (Medknow Publications & Media Pvt Ltd, 2014)
Malignant fibrous histiocytoma (MFH) a pleomorphic sarcoma of uncertain origin was first described by O’Brien and Stout in 1964. It is the most common primary soft tissue sarcoma of late adult life; its occurrence is rare in the pediatric population. MFHs are commonly known to arise in the extremities and the trunk although it can occur almost anywhere in the body. MFH of the scalp is extremely rare; moreover, there is paucity of literature with regards to prevalence of scalp and skull neoplasms. We present an unusual case of a primary MFH involving the scalp of a 5-year-old child and discuss its unusual clinical presentation, histology with immunohistochemistry correlation and its management. Reviewing the literature of primary MFH of the scalp, our patient to the best of our knowledge, is probably the youngest case reported so far.